Magnetic resonance imaging-guided transurethral ultrasound ablation of prostate tissue in patients with localized prostate cancer: single-center evaluation of 6-month treatment safety and functional outcomes of intensified treatment parameters - Hatiboglu, Gencay; Bonekamp, David; Pahernik, Sascha; Tosev, Georgi; Radtke, Jan Philipp; Motsch, Johann; Schlemmer, Heinz-Peter; Hohenfellner, Markus; Nyarangi-Dix, Joanne (World journal of urology, 2020)
To evaluate the effect of intensified treatment parameters on safety, functional outcomes, and PSA after MR-Guided Transurethral Ultrasound Ablation (TULSA) of prostatic tissue. Baseline and 6-month follow-up data were collected for a single-center cohort of the multicenter Phase I (n = 14/30 at 3 sites) and Pivotal (n = 15/115 at 13 sites) trials of TULSA in men with localized prostate cancer. The Pivotal study used intensified treatment parameters (increased temperature and spatial extent of ablation coverage). The reporting site recruited the most patients to both trials, minimizing the influence of physician experience on this comparison of adverse events, urinary symptoms, continence, and erectile function between subgroups of both studies. For Phase I and TACT patients, median age was 71.0 and 67.0 years, prostate volume 41.0 and 44.5 ml, and PSA 6.7 and 6.7 ng/ml, respectively. All 14 Phase I patients had low-risk prostate cancer, whereas 7 of 15 TACT patients had intermediate-risk disease. Baseline IIEF, IPSS, quality of life, and pad use were similar between groups. Pad use at 1 month and quality of life at 3 months favored Phase I patients. At 6 months, there were no significant differences in functional outcomes or adverse events. TULSA demonstrated acceptable clinical safety in Phase I trial. Intensified treatment parameters in the TACT Pivotal trial increased ablation coverage from 90 to 98% of the prostate without affecting 6-month adverse events or functional outcomes. Long-term follow-up and 12-month biopsies are needed to evaluate oncological safety.
Published online: 06 May 2019
Gesehen am 02.03.2020